Prevalence and clinical profile of patients with resistant hypertension - Uma maheswari B.; Suganya P.; Revathi A. (International Journal of Medical Research and Review, 2019)
Objective: To find prevalence and clinical profile of patients with resistant hypertension.Methods: In a Prospective Observational Study, 100 Hypertensive patients were evaluated in Hypertension OPD, Medical OPD, and Medical Wards. Hypertensive Patient on more than 3 drugs with uncontrolled BP were included for this study. Patients were subjected to Clinical examination, Laboratory investigations and Ultrasound. BP is recorded in all 4 limbs with appropriate cuff size, Patients drug history (Both antihypertensive and other medications for concomitant illness will be enquired), Physical activity and Drug compliance were enquired.Result: Among the 100 patients studied, 18% patients were found to have Resistant hypertension. Of this, 5 patients were in incorrect drug combination, 7 patients were not drug compliant, 12 patients had Uncontrolled Diabetes, 15 patients had Dyslipidemia, 6 patients had Medical Renal disease, 2 patients had Fatty Liver, 1 patient had Contracted Kidney and 1 patient had Aortailiac Thrombosis.Conclusion: Incorrect Drug prescription, non-adherence to drugs and metabolic factors played a major role in resistant hypertension in the present study group.